Knowledge Management Enablers Toward Successful New Product Development: A Case Study In A Semiconductor Manufacturing Firm - Sin, Chong Hai; Goh, Gerald Guan Gan; Eze, Uchenna Cyril (Journal of Knowledge Management Practice, 2009)
Knowledge management has been regarded as a key factor in enhancing organisational performance in organisations across the globe. The pivotal role of knowledge management is more pronounced in knowledge-intensive organisations such as those involved in research and development, and new product development. Using a case study of large semiconductor manufacturing firm in Malaysia, this study examines the role of knowledge management enablers in enhancing the performance of the organisation. It specifically looks at the four broad categories of knowledge management enablers identified from the extant literature which are strategy and leadership, corporate culture, people and information technology. Interviews, observation and document review were among the tools used to elicit information collected for further analysis. The results supports the findings obtained from previous studies regarding the role of these four knowledge management enablers when implementing a KM programme within an organisation. Interestingly, this study found that that both talent and succession management helps to retain much needed expertise and knowledge apart from keeping long-term as well as committed connections within the organisations knowledge workers.